Income Tax 21, Understanding, Subject, And Calculation Of Tax On Taxpayer's Income - Fayakhun Wibisono; Rahmadi Zikri Chandra; Zahira Naswa; Ramadani Ramadani; Rizky Natasya; Galih Supraja; Hafidz Sagala (International Journal of Economic Research and Financial Accounting, 2025)
This article aims to explain that income tax 21 is a tax imposed by domestic taxpayers who are usually in the form of salaries, wages, allowances, and other payments. this article also provides a thorough understanding of the subject, object, and calculation of income tax 21 (PPH 21). This article uses a quantitative descriptive approach method, because this method is suitable for exploring, explaining, and analyzing various concepts related to income tax 21. the results of the discussion of this article provide us with insight into the importance of understanding income tax 21 for employers and employees in fulfilling their obligations as taxpayers in accordance with Indonesian tax regulations and by knowing how the income tax 21 mechanism we can avoid errors in tax withholding and reporting. this article explains how income tax 21 is subject to progressive rates ranging from 5% to 35% rates depending on the amount of Taxable Income (PKP)